Evaluation of Artemisia amygdalina D. for Anti-Inflammatory and Immunomodulatory Potential. (10th October 2013) - Mubashir, Khan; Ganai, Bashir A.; Ghazanfar, Khalid; Akbar, Seema; Malik, Akhtar H.; Masood, Akbar
Abstract : Artemisia amygdalina D. is a critically endangered endemic medicinal plant of Kashmir Himalayas. In the current study anti-inflammatory and immunomodulatory activity of the plant was carried out. Carrageenan paw edema model was used to study the potential of the drug in inflammation in Wistar rats. SRBC-specific haemagglutination titre and DTH assays were carried out in Balb/C mice for observing the effect of test drugs on immune system. The plant extracts used as test drugs showed to have anti-inflammatory potential. The methanolic fraction was observed to have the maximum effect on the inhibition of paw edema formation with the inhibitory potential of 42.26%, while in the immunomodulation studies the test drugs were found to have the immunosuppressant activity with methanolic fraction again showing the maximum potential for the suppression of both humoral (55.89% and 47.91%) and cell-mediated immunity (62.27% and 57.21%). The plant in total seems to have the anti-inflammatory potential. The suppression of immune system suggests some mechanistic way by which the inhibition of inflammation takes place. Since, in chronic inflammation like arthritis, there is the involvement of immune system, the plant in that way may serve as an alternative for the treatment of such autoimmune diseases.